Influence of the gregarious instinct and individuals' behavior patterns on macro migrations: Simulation experiments. Issue 2 (17th February 2018) - Raczynski, Stanislaw
ABSTRACT: The objective of the model is to simulate the migrations of social groups over certain geographical regions, influenced by the gregarious effect and individual behavior patterns. The people move in search of better work opportunities and welfare. The model components are regions and individuals belonging to certain social groups. A region is characterized by more than 30 parameters, such as geographical data, actual population statistics, education facilities, and work opportunities. For the social groups, the parameters include the demographic and educational statistics. The simulated individuals attempt to optimize their welfare by moving over the model map. Spontaneous migration, without apparent goal, is also considered. The region parameters change owing to the number and the parameters of incoming individuals, which provides a dynamic and nonlinear feedback. The qualitative results reveal that the model never reaches a steady state and that the social groups remain in periodical movement. The simulations are agent-based. No differential equations (like in the System Dynamics approach) or any extant theory or mathematical model is used.